Construction Supply Chain Management Handbook. - O'Brien, William J. (Taylor & Francis Ltd., 2008)
Increasing demands for quality, cost, and speech improvements as well as the revolution in global logistics brought research on construction supply chain management to the forefront. This book addresses major areas of concern, including management of production operations and organizational arrangements and contracts.